The Design of Mobile Indoor Robot Guidance System - Dhanny Kurniawan Haryanto; Kanisius Karyono; Samuel Hutagalung (IJNMT (International Journal of New Media Technology), 2018)
The mobile indoor robot guidance system is a mobile robot which can assist users to find the desired position or location indoor or inside particular shed where Global Position System (GPS) failed to perform. Robot guidance system has many features in order to make the system useful for all of the users. The type of user who can make use of this system is mostly the disabled user and the user which is unfamiliar with the environment or the map. There is also potential usage inside the shopping mall or the big office spaces with the capability of displaying the advertisement during guidance process. This work deploys robot guidance system using geo-magnetic and Wifi methods for Indoor Positioning System (IPS). Although DC motors can generate interference to the magnetic sensor, the proper shields are adequate for the system. The metal shields for the DC motor can minimize the deviation from 6.41n T or about 16.74% for non-shielding motors to 2.86 n T or about 10.56%. Based on this research, mobile indoor robot guidance system can be implemented using various methods of IPS including geo-magnetic. Index Terms—mobile robot, indoor positioning system (IPS), Wifi multilateration, geo-magnetic positioning, disabled user.